Análise bibliométrica de green supply chain management - Gumieri, Jean Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Due to the high competitiveness and dynamism of the current market, the rapid evolution of technology and globalization, companies are increasingly looking for innovations that will put them ahead of their competitors in this consumer dispute. One of the themes that has been most prominent today is the adoption of sustainable practices and cleaner production, making these companies have an advantage both in their waste and demonstrating to their consumers a commitment to sustainable development long term. Following these lines, some supply chain management (SCM) practices have assumed the character of green supply chain management (GSCM), in order to minimize environmental impacts in the supply chain, increasing ecological efficiency, aiming for long term wellbeing, through corporate sustainability. In this work, a bibliometric research was done to identify how much the subject has been studied in the current literature, and to search for gaps in this literature that will aid future research, allowing the theme to be increasingly dissipated

Devido à alta competitividade e dinamismo do mercado atual, a rápida evolução da tecnologia e a globalização, empresas buscam cada vez mais inovações que a coloquem a frente de suas concorrentes nessa disputa pelo consumidor. Um dos temas que mais tem tido destaque na atualidade, é a adoção de práticas sustentáveis e uma produção mais limpa, fazendo com que essas empresas tenham uma vantagem, tanto nos seus desperdícios, como também demonstrando para seu consumidor um comprometimento com o desenvolvimento sustentável a longo prazo. Seguindo essa linha, algumas práticas de supply chain management (SCM) assumiram um caráter de green supply chain management (GSCM), de forma a minimizar os impactos ambientais na cadeia de suprimentos, aumentando a eficiência ecológica, visando o bem estar a longo prazo, através da sustentabilidade empresarial. Nesse trabalho, foi feita uma pesquisa bibliométrica acerca do tema, para identificar o quanto o assunto tem sido estudado na literatura atual, e buscar gaps nessa literatura que auxiliem pesquisas futuras, permitindo que o tema seja cada vez mais dissipado
Bibliometric analysis of green supply chain management
Keywords: Controle de estoque; Desenvolvimento sustentável; Cadeia de logística integrada; Inventory control